Mean Corneal Endothelial Cell Loss in Type 2 Diabetic Cataract Patients After Phacoemulsification. - Mazhar, Syed Abdullar; Zahid, Sehar; Hanif, Junaid; Arshad, Muhammad Asharib; Iqbal, Rana Naveed (Pakistan Journal of Ophthalmology, 2020)
Purpose: To assess the mean corneal endothelial cell loss after Phacoemulsification in patients of type 2 diabetes. Study Design: Cross-sectional study. Place and Duration of Study: Layton Rahmatullah Benevolent Trust Free Eye and Cancer Hospital for a period of six months, from May 2015 to November 2015. Material and Methods: Three hundred and fifty-five patients were selected by non-probability convenience sampling. Patients with cataract, diagnosed at least after 6 months of diagnosis of type 2 diabetes were included in this study. Patients with any systemic disease or ocular disease other than senile cataract were excluded from the study. Endothelial cell count was measured with Specular microscopy one day before surgery. One experienced surgeon with post-graduate experience of at least five years performed all the procedures. Follow up by specular microscopy was done at 6 weeks after phacoemulsification. Statistical analysis was done using SPSS version 23. Results: Mean age of the patients was 59.32 ± 7.60 years. There were 41.97% males and 58.03% females. Mean endothelial cell count before phacoemulsification was 2177.21 ± 591.078 and 6 weeks after surgery was 1984 ± 597.51. Age, gender, laterality, duration of diabetes and type of cataract was not significantly related with endothelial cell loss, p-value > 0.05. Mean endothelial cells loss was higher in patients with HbA1c > 7 as compared to those with HbA1c < 7 (p-value = 0.01). Conclusion: Patients with poor control of diabetes have higher endothelial cell loss after phacoemulsification than patients with good control.